2021
DOI: 10.1111/are.15540
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of moderate dietary cellulose against antibiotic‐induced growth retardation, blood deterioration and immunosuppression in juvenile yellow catfish ( Pelteobagrus fulvidraco)

Abstract: The long‐term use of antibiotics causes multiple side effects. It is vital to find substances that mitigate these side effects. The aims of this study were to investigate the effects of antibiotic stress on the growth and health of yellow catfish and to evaluate the protective effect of supplemented cellulose diets. In this study, the fish were randomly distributed into four groups as follows: Control group (fed with no cellulose), Anti group (fed with antibiotics alone), Anti + MC group (fed with antibiotics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…99 In recent years, aquatic nutritionists have conducted many studies related to mitigating the harmful effects of antibiotics on aquatic animals through nutritional strategies, such as using cellulose and increased carbohydrate level in diets. 17,100 However, in general, there are relatively few studies exploring the relationship between nutrition and the environment in aquaculture in China. Compared with livestock feed, aquafeed has higher requirements in terms of crushing size, steam conditioning, and pellet appearance.…”
Section: Environmentally Friendlymentioning
confidence: 99%
See 1 more Smart Citation
“…99 In recent years, aquatic nutritionists have conducted many studies related to mitigating the harmful effects of antibiotics on aquatic animals through nutritional strategies, such as using cellulose and increased carbohydrate level in diets. 17,100 However, in general, there are relatively few studies exploring the relationship between nutrition and the environment in aquaculture in China. Compared with livestock feed, aquafeed has higher requirements in terms of crushing size, steam conditioning, and pellet appearance.…”
Section: Environmentally Friendlymentioning
confidence: 99%
“…More importantly, one study reported a direct human health risk linked to the consumption of fish treated with antibiotics in children 99 . In recent years, aquatic nutritionists have conducted many studies related to mitigating the harmful effects of antibiotics on aquatic animals through nutritional strategies, such as using cellulose and increased carbohydrate level in diets 17,100 . However, in general, there are relatively few studies exploring the relationship between nutrition and the environment in aquaculture in China.…”
Section: Current Achievements Of the Aquatic Animal Nutrition And Fee...mentioning
confidence: 99%